Pengaruh Model Pembelajaran Advance Organizer Berbantuan Peta Konsep Terhadap Hasil Belajar Fisika Siswa SMA Negeri 1 Lingsar - Raeha Nopiani; Ahmad Harjono; Hikmawati Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
This study aims to determine the effect of advanced organizer learning model using concept mapping on studentÃ¢â¬â¢s physics learning achievement SMA Negeri 1 Lingsar. This research type is quasi experiment with pretest-posttest control group design. The population of this study is all students of class XI IPA SMA Negeri 1 Lingsar with sampling technique using purposive sampling. The classes that sampled are class XI IPA 2 as experiment class and class XI IPA 1 as control class. The results of study are learning outcome in the cognitive aspect while affective and psychomotor aspect as supporting data. The instrument was used to measure the learning outcome of the cognitive aspect is an objective test. The result of prerequisite analysis test shows that posttest data are normal and homogeneous distributed so that statistic test used is parametric statistic t-test poled varian with t test criteria of two parties, and obtained = 2.19 and ÃÂ = 1.99 at 5% significant level. ThereforeÃÂ  >ÃÂ  ÃÂ then ÃÂ is rejected and ÃÂ is accepted, it can be concluded that there is the effect of advanced organizer learning model using concept mapping on studentÃ¢â¬â¢s physics learning achievement SMA Negeri 1 Lingsar.